Factors Influencing Consumer Buying Behavior Towards Organic Millets And Pulses In Hyderabad City – A Study - S.V.Suresh Raju and Dr. A. Rukmani (International journal of economic perspectives, 2022)
India’s organic food and beverage consumption has grown in recent years due to its advanced demographic dividend, improved purchasing power and increased interest for the perceived health and wellness benefits of certain organic products. The popularity of organically grown foods is increasing day by day owing to their nutritional and health benefits. The Indian economy still depends on agriculture which contributes 19.9 % to the GDP of the country where 60% of the people relying on agriculture in 2020- 2021. India has 30 percent of total certified organic producers in the world, but accounts for just 3.3 percent (1.9 million hectares) of total organic cultivated area at 57.8 million hectares.The main objective of the study is to analyze the factors influencing consumer buying behavior towards organic food products. This study is conducted in Hyderabad city of Telangana state and restricted to the geographical region of GHMC area. This study organized to contribute to bridge the knowledge gap by investigating the various perspectives of Organic food products from Consumers point of view. The current study applies both qualitative and quantitative research technique, i.e., in short it encompasses of both explorative and descriptive research. First stage of the research was exploratory in nature. Explorative research formed part of desk work carried out for collection of review of literature. A descriptive research is carried out at the second stage of the study by applying a survey method. A questionnaire was developed and administered to 500 consumers by using convenient sampling. Final sample size was confirmed to 416 as an 83.20% response rate under the study. Factor analysis, chi-square and descriptive statistics are used to analyze the data collected from consumes. The results show that there are two components extracted from seven factors viz., Health Maintenance and Nutrition and Decease prevention labels. Further, there is a need to conduct similar kinds of research in other areas of Hyderabad city as well as Inter – Districts of Telangana state to measure the consumer preference and satisfaction towards organic millets and pulses.